2021
DOI: 10.1111/ajt.16617
|View full text |Cite
|
Sign up to set email alerts
|

The organ procurement costs of expanding deceased donor organ acceptance criteria: Evidence from a cost function model

Abstract: The shortage of available organs represents a large public health crisis worldwide, including in the United States. 1 One solution is to expand living donation for organs where possible. Another solution is to expand deceased donor organ utilization. The expansion of deceased donor criteria has been an active area of recent research. Comparative studies between the United States and other developed countries including the United Kingdom, Spain, and France have shown that nonstandard donors, including older don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Therefore, the cost of the DDKT group might be underestimated. Cheng et al (30) reported the estimated organ procurement costs from DDKT using cost function model to demonstrated cost projection. They found that procurement cost of kidney from single-organ transplantation resulted 55,000 USD per kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the cost of the DDKT group might be underestimated. Cheng et al (30) reported the estimated organ procurement costs from DDKT using cost function model to demonstrated cost projection. They found that procurement cost of kidney from single-organ transplantation resulted 55,000 USD per kidney.…”
Section: Discussionmentioning
confidence: 99%
“…We previously used this approach to estimate the costs of dialysis and hospital services for Medicare beneficiaries 9,10 and the costs of procuring organs at an organ procurement organization level. 11 Figure 1 illustrates the cost function framework as applied to the pretransplant setting. 12 which enabled us to create, at the transplant hospital level, proxy measures for transplant hospital processes (eg, number of waitlist additions at each hospital each year) and case-mix indicators (eg, percent of incident waitlist patients with diabetes mellitus).…”
Section: General Approach and Cost Functionmentioning
confidence: 99%
“…It is therefore impossible to directly deduce what each transplantation-specific service costs. Part of our future direction is to apply a cost function approach, as has been applied to dialysis modalities 22 and organ procurement costs, 23 to estimate the costs of each transplant-specific service.…”
Section: Limitationsmentioning
confidence: 99%